2022
DOI: 10.3389/fpsyt.2022.842936
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Time of Admission, Help-Seeking Behavior, and Psychiatric Outcomes: “From Dusk Till Dawn”

Abstract: IntroductionDay and time of admission influence treatment outcomes and prognosis in several medical specialties; this seems related to resources' ability. It is largely unknown whether this also applies to mental health services. We investigate the relationship between time of admission, patients' demographic and clinical profile, and treatment outcomes.MethodsDemographic and clinical profiles of admitted and discharged patients to a general psychiatric ward between January 1st, 2013 and December 31st, 2020, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Client profiles and behaviors could also vary throughout the day, which could lead to different outcomes. In a study of psychiatric patients, patients admitted on night shifts have more acute symptoms and are given a shorter length of stay and higher rates of coercive measures (Knorr et al, 2022). In order to account for the potential effects of visiting hours, we categorized the clients’ visiting hours into three 8-hr shifts: late night shift (1 a.m. to 8 a.m.), day shift (9 a.m. to 4 p.m.), and evening shift (5 p.m. to midnight).…”
Section: Methodsmentioning
confidence: 99%
“…Client profiles and behaviors could also vary throughout the day, which could lead to different outcomes. In a study of psychiatric patients, patients admitted on night shifts have more acute symptoms and are given a shorter length of stay and higher rates of coercive measures (Knorr et al, 2022). In order to account for the potential effects of visiting hours, we categorized the clients’ visiting hours into three 8-hr shifts: late night shift (1 a.m. to 8 a.m.), day shift (9 a.m. to 4 p.m.), and evening shift (5 p.m. to midnight).…”
Section: Methodsmentioning
confidence: 99%
“…A multi-center investigation of twenty acute psychiatric units in Norway found that IA happened more often during evenings and nights and by physicians who did not know the PMHC [45]. Two separate Swiss studies reported that involuntary admissions occurred more often at night time and during the weekends [46,47]. The link between "daytime hours" and fewer IAs was attributed to a combination of demographics, clinical features, and out-of-clinic service availability (such as ambulatory psychiatric-psychological praxis; day-clinic; and home treatment) [46].…”
Section: Temporal Factorsmentioning
confidence: 99%
“…Two separate Swiss studies reported that involuntary admissions occurred more often at night time and during the weekends [46,47]. The link between "daytime hours" and fewer IAs was attributed to a combination of demographics, clinical features, and out-of-clinic service availability (such as ambulatory psychiatric-psychological praxis; day-clinic; and home treatment) [46]. A German study likewise discovered that cases admitted unwillingly were admitted more frequently at night or on weekends [36].…”
Section: Temporal Factorsmentioning
confidence: 99%